Filtration Challenges in Non-Alcoholic and Low-Alcohol Beer Production with a Focus on Different Yeast Strains - Christian Schubert; Jörg Maxminer; Matthew Aitkens; Andrew Maust; Bernardo Pontes Guimarães; Rahul Sen; Scott Lafontaine (Applied Sciences, 2025)
This study examines the impact of yeast selection on fermentation performance, filtration efficiency, and the stability of low-alcohol and non-alcoholic beer (NAB). Three yeast strains (LA-01, LoNa, and W-34/70) were evaluated for their effects on key NAB parameters like ABV, bitterness, color, haze readings, and filtration-linked performance. Filtration trials revealed that highly flocculating W-34/70 resulted in lower post-filtration turbidity, whereas LA-01 and LoNa (which flocculated less) required more effective filtration techniques to achieve clarity. Among the tested filter sheets, AF 31, AF 71, and AF 101 successfully reduced turbidity below 2 EBC. However, all NABs exhibited haze formation during storage, indicating the necessity of stabilization treatments. These findings highlight the importance of yeast strain selection and filtration strategies in optimizing NAB production. Additional pretreatment steps, such as centrifugation, may improve filterability for non-flocculating yeasts, while stabilization measures are essential for maintaining long-term clarity. This study provides valuable insights for improving industrial NAB processing and quality.